Microplegia versus Cardioplexol® in Coronary Artery Bypass Surgery with Minimal Extracorporeal Circulation: Comparison of Two Cardioplegia Concepts - Koechlin, Luca; Rrahmani, Bejtush; Gahl, Brigitta; Berdajs, Denis; Grapow, Martin T.R.; Eckstein, Friedrich S.; Reuthebuch, Oliver (The Thoracic and Cardiovascular Surgeon, 2020)
Background The aim of this study is to compare the combined use of the Myocardial Protection System and our microplegia (Basel Microplegia Protocol) with Cardioplexol® in coronary artery bypass grafting using the minimal extracorporeal circulation.Methods The analysis focused on propensity score matched pairs of patients in whom microplegia or Cardioplexol® was used. Primary efficacy endpoints were high-sensitivity cardiac troponin-T on postoperative day 1 and peak values during hospitalization. Furthermore, we assessed creatine kinase and creatinine kinase-myocardial type, as well as safety endpoints.Results A total of 56 patients who received microplegia and 155 patients who received Cardioplexol® were included. The use of the microplegia was associated with significantly lower geometric mean (confidence interval) peak values of high-sensitivity cardiac troponin-T (233 ng/L [194–280 ng/L] vs. 362 ng/L [315–416 ng/L]; p = 0.001), creatinine kinase (539 U/L [458–633 U/L] vs. 719 U/L [645–801 U/L]; p = 0.011), and creatinine kinase-myocardial type (13.8 µg/L [9.6–19.9 µg/L] vs. 21.6 µg/L [18.9–24.6 µg/L]; p = 0.026), and a shorter length of stay on the intensive care unit (1.5 days [1.2–1.8 days] vs. 1.9 days [1.7–2.1 days]; p = 0.011). Major adverse cardiac and cerebrovascular events occurred with roughly equal frequency (1.8 vs. 5.2%; p = 0.331).Conclusions The use of the Basel Microplegia Protocol was associated with lower peak values of high-sensitivity cardiac troponin-T, creatinine kinase, and creatinine kinase-myocardial type and with a shorter length of stay on the intensive care unit, as compared with the use of Cardioplexol® in isolated coronary artery bypass surgery using minimal extracorporeal circulation.
Keywords: cardiopulmonary bypass (CPB); coronary artery bypass grafts surgery (CABG); myocardial protection/cardioplegia; perfusion